Strategi Pengelolaan Media Sosial untuk Meningkatkan Citra Perusahaan PLN Icon Plus - Gusvandi Harki; Alfi Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
The advancement of technology has made social media a strategic platform for companies, including PLN Icon Plus, to build corporate image and reputation through public interaction and the promotion of Corporate Social and Environmental Responsibility (TJSL) programs. This study aims to identify and analyze effective social media management strategies and measure their effectiveness in improving the company's image. Employing a qualitative approach, data was collected through in-depth interviews, observation, and content analysis on the PLN Icon Plus platform, conducted from August 19 to December 20, 2025. The findings indicate that the implemented strategies, which include rapid interaction, the use of engaging visuals (especially reels focusing on TJSL), collaboration with national news media, and publication of achievements, are proven effective. Instagram insights analysis showed a significant increase in content views, reach, and interaction from August to November 2025. The study concludes that proper social media management is essential for building a positive image, with implications for the need for continuous content innovation, active audience interaction, and routine evaluation to achieve future business goals.